Running of the charm-quark mass from HERA deep-inelastic scattering data - Gizhko, Andrii; Jung, Andreas Werner; Lisovyi, Mykhailo; Geiser, Achim (Physics letters, 2017)
Combined HERA data on charm production in deep-inelastic scattering have previously been used to determine the charm-quark running mass mc(mc) in the MS‾ renormalisation scheme. Here, the same data are used as a function of the photon virtuality Q2 to evaluate the charm-quark running mass at different scales to one-loop order, in the context of a next-to-leading order QCD analysis. The scale dependence of the mass is found to be consistent with QCD expectations.